2013
DOI: 10.1242/dev.103010
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation and remodeling of post-embryonic C. elegans cells by a single transcription factor

Abstract: Terminally differentiated post-mitotic cells are generally considered irreversibly developmentally locked, i.e. incapable of being reprogrammed in vivo into entirely different cell types. We found that brief expression of a single transcription factor, the ELT-7 GATA factor, can convert the identity of fully differentiated, highly specialized non-endodermal cells of the pharynx into fully differentiated intestinal cells in intact larvae and adult Caenorhabditis elegans. Stable expression of intestine-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…As reported previously, we confirmed that END-1 is not capable of activating expression of late markers of intestine differentiation in the pharynx (Fig. 1B; Zhu et al, 1997; Zhu et al, 1998; Riddle et al, 2013). As ELT-7 is the smallest of the endoderm GATA factors, it was conceivable that either its size, or some unique structural characteristic, endows it with the ability to access promoters contained in otherwise inaccessible chromatin within differentiated cells.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As reported previously, we confirmed that END-1 is not capable of activating expression of late markers of intestine differentiation in the pharynx (Fig. 1B; Zhu et al, 1997; Zhu et al, 1998; Riddle et al, 2013). As ELT-7 is the smallest of the endoderm GATA factors, it was conceivable that either its size, or some unique structural characteristic, endows it with the ability to access promoters contained in otherwise inaccessible chromatin within differentiated cells.…”
Section: Resultssupporting
confidence: 92%
“…We observed widespread ELT-2::GFP expression in most tissues as early as 4 h, as previously reported (Fig. 3; Riddle et al, 2013). IFB-2 expression is first observed in the pharynx 8–12 h after ectopic ELT-7 expression, and in the somatic gonad at approximately 12 h (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations